The Final Days of the Franklin Expedition: New Skeletal Evidence - Keenleyside, Anne; Bertulli, Margaret; Fricke, Henry C. (ARCTIC, 1997)
In 1992, a previously unrecorded site of Sir John Franklin's last expedition (1845-1848) was discovered on King William Island in the central Canadian Arctic. Artifacts recovered from the site included iron and copper nails, glass, a clay pipe fragment, pieces of fabric and shoe leather, buttons, and a scatter of wood fragments, possibly representing the remains of a lifeboat or sledge. Nearly 400 human bones and bone fragments, representing a minimum of 11 men, were also found at the site. A combination of artifactual and oxygen isotope evidence indicated a European origin for at least two of these individuals. Skeletal pathology included periostitis, osteoarthritis, dental caries, abscesses, antemortem tooth loss, and periodontal disease. Mass spectroscopy and x-ray fluorescence revealed elevated lead levels consistent with previous measurements, further supporting the conclusion that lead poisoning contributed to the demise of the expedition. Cut marks on approximately one-quarter of the remains support 19th-century Inuit accounts of cannibalism among Franklin's crew. En 1992, on a découvert un site non mentionné auparavant, relié à la dernière expédition de sir John Franklin (1845-1848) dans l'île du Roi-Guillaume, située au centre de l'océan Arctique canadien. Les artefacts récupérés sur ce site comprenaient des clous en fer et en cuivre, du verre, un fragment de pipe en terre, des morceaux de tissu et de cuir de chaussure, des boutons et de multiples fragments de bois éparpillés, qui pourraient venir d'un canot de sauvetage ou d'un traîneau. On a aussi trouvé sur le site un total d'environ 400 fragments osseux ou os complets, représentant au moins 11 hommes. En se basant à la fois sur de la documentation archéologique et sur des analyses des isotopes de l'oxygène, on a pu attribuer une origine européenne à au moins deux de ces individus. Les lésions osseuses comprenaient périostites, ostéo-arthrite, caries dentaires, abcès, perte de dents précédant le décès et parodontolyses. La spectroscopie de masse et ...